1993
DOI: 10.1002/job.4030140105
|View full text |Cite
|
Sign up to set email alerts
|

The measurement properties of the role conflict and role ambiguity scales: A review and extension of the empirical research

Abstract: The measurement properties of the Rizzo, House and Lirtzman (1970) role conflict and role ambiguity scales have been debated in the research literature for several years. The criticisms are that the scales do not measure separate constructs and are contaminated by method variance. However, some researchers have presented evidence supporting the scales' continued use as independent measures. We attempted to clarify the running debate by re-examining these issues and presenting additional data, which focused on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 17 publications
1
23
0
2
Order By: Relevance
“…This method has been used in several other studies which have demonstrated that survey data collected via trained undergraduates (the approach used in this study) are of comparable quality to more traditional data collection procedures such as collecting data via researchers within an organization (e.g. Hazer & Highhouse, 1997; Smith & Sulsky, 1995; Smith, Tisak, Hahn, & Schmieder, 1997; Smith, Tisak, & Schmieder, 1993).…”
Section: Methodsmentioning
confidence: 99%
“…This method has been used in several other studies which have demonstrated that survey data collected via trained undergraduates (the approach used in this study) are of comparable quality to more traditional data collection procedures such as collecting data via researchers within an organization (e.g. Hazer & Highhouse, 1997; Smith & Sulsky, 1995; Smith, Tisak, Hahn, & Schmieder, 1997; Smith, Tisak, & Schmieder, 1993).…”
Section: Methodsmentioning
confidence: 99%
“…Perceptions of distributive fairness were assessed by three items adapted from a five-item distributive justice measure developed by Price and Mueller (1986) to suit the focus on family members' perceptions (a = 0.96). Finally, for role ambiguity we utilized a shortened three-item measure adapted from Smith et al (1993) that measures the degree of a respondent's role clarity; the construct exhibited a satisfactory alpha (a = 0.84). Responses were reverse scored so that lower scores on the measure indicate higher levels of the respondent's role ambiguity.…”
Section: Independent Variablesmentioning
confidence: 99%
“…While the scale is nearly four decades old, House, Schuler, and Levanoni (1983) conducted a replication study and found that the original scale has sufficient reliability and validity. In fact, Rizzo et al's (1970) scale is considered by many researchers to be an acceptable measure of role ambiguity (i.e., Boles & Babin, 1994;Harris & Bladen, 1994;Netemeyer, Johnston, & Burton, 1990;Smith, Tisak, & Schmeider, 1993).…”
Section: Job Design Measuresmentioning
confidence: 99%